(untitled) (Journal of the College of Basic Education, 2022)
The aim of this study was to characterize,biotyping and genotyping of Cronobacter sakazakii previously isolated from a range of foods .Some virulence factors of 6 Cronobacter sakazakii were tested .All the isolates (6) were capsule formation,capable of producing biofilm,Lipase,gelatinase and protease production.Most of the isolates have hemolytic activity,while none of the isolates have the ability to hydrolyze starch or produce lecithinase.The effect of some physical and biological factors on growth of Cronobacter sakazakii were also studied.Optimum temperature was 40ºC for (3) isolates ,while 37ºC for (2) isolates and 30ºC for (1) isolate.Optimum pH was 5 for (4) isolates ,while (2) isolates gave highest growth at pH 7.An agar well diffusion method was used to assess the antibacterial activity of Lactobacillus fermentum against Cronobacter sakazakii diameter of inhibition zone was ranged between 15-25 mm.Some biochemical tests were performed in order to biotype the isolates .The 6 isolates were distributed in to two biotypes,biotype 1 and biotype 11.BOX-PCR fingerprinting technique was used to genotype Cronobacter sakazakii food isolates.Three isolates (50%) were belong to different genotypes (this may be due to the differences in the source of isolation) ,and the other three isolates (50%) were belong to genotype with closely related patterns of fingerprints (two of strains were isolated from the same type of food sample).